2009
DOI: 10.1590/s0100-67622009000600008
|View full text |Cite
|
Sign up to set email alerts
|

Síndromes de dispersão de sementes em três trechos de vegetação ciliar (nascente, meio e foz) ao longo do rio Pindaíba, MT

Abstract: RESUMO -Este estudo foi desenvolvido visando identificar as proporções entre as síndromes de dispersão e os tipos de frutos encontrados em três áreas: nascente (Cerrado Rupestre), meio e foz (mata ciliar -Floresta Estacional Semidecidual) ao longo do Rio Pindaíba, MT. No trecho de nascente, 55,6% das espécies amostradas eram zoocóricas, 43% anemocóricas e apenas 1,4% autocóricas, respectivamente. No trecho do meio, 85,7% das espécies eram zoocóricas, 11,7% anemocóricas e apenas 1,3% autocóricas. Na foz do Rio … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
12

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 14 publications
1
2
0
12
Order By: Relevance
“…The proportion of dispersal classes found for seeds in the present work agrees with other studies about the main classes of dispersal in the Atlantic Forest, which reported a predominance of zoochory, followed by anemochory and autochory (Spina et al 2001;Sales et al 2007;Silva and Rodal 2009;Stefanello et al 2009). The multiple logistics regression suggests that physical dormancy is more likely to occur in seeds dispersed by autochory.…”
Section: Discussionsupporting
confidence: 92%
“…The proportion of dispersal classes found for seeds in the present work agrees with other studies about the main classes of dispersal in the Atlantic Forest, which reported a predominance of zoochory, followed by anemochory and autochory (Spina et al 2001;Sales et al 2007;Silva and Rodal 2009;Stefanello et al 2009). The multiple logistics regression suggests that physical dormancy is more likely to occur in seeds dispersed by autochory.…”
Section: Discussionsupporting
confidence: 92%
“…A predominância da zoocoria tem sido relacionada como a principal síndrome de dispersão de matas ciliares em florestas tropicais e nos Cerrados brasileiros (BUDKE et al, 2005;De MARCHI, 2005;STEFANELLO et al, 2009STEFANELLO et al, , 2010SCARIOT;REIS, 2010;SILVA et al, 2012). Essas formações permitem a manutenção de fauna que busca refúgio, alimento e água (MARINHO-FILHO; GASTAL, 2000), assim favorecendo a zoocoria nesses ambientes (STEFANELLO et al, 2009).…”
Section: Discussionunclassified
“…Moreover, the species studied were also classified according to seed dispersal syndrome (Table 1), following van der Pilj (1982) classification, in zoochorous, when the dispersal is done by animals; anemochorous, when the dispersion is carried by the wind; and autochorous, when the dispersion occurs by explosive dehiscence or gravity. The species classification was made according to information on the biology of the species found in literature (Briton & Rose 1963;Maia 2004;Barbosa 2005;Barbosa et al 2005;Santos et al 2005;Pereira et al 2008;Moreira et al 2009;Silva & Rodal 2009;Stefanello et al 2009;Maragon et al 2010), expert consultation and increased knowledge of the authors. This classification was intended to detect patterns related to reproductive strategies of species.…”
Section: Data Analysesmentioning
confidence: 99%